2020
DOI: 10.1016/j.stemcr.2020.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt Pathway Controls mESC Self-Renewal Through Inhibition of Spontaneous Differentiation via β-Catenin/TCF/LEF Functions

Abstract: The Wnt/b-catenin signaling pathway is a key regulator of embryonic stem cell (ESC) self-renewal and differentiation. Constitutive activation of this pathway has been shown to increase mouse ESC (mESC) self-renewal and pluripotency gene expression. In this study, we generated a novel b-catenin knockout model in mESCs to delete putatively functional N-terminally truncated isoforms observed in previous knockout models. We showed that aberrant N-terminally truncated isoforms are not functional in mESCs. In the ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 31 publications
7
29
0
Order By: Relevance
“…teratomas from the mutants with the highest β -catenin transcriptional activity showed major differentiation defects in the neuroectoderm, dorsal mesoderm and endoderm lineages. Of note, results in (Kielman et al, 2002) (Lyashenko et al, 2011, Wray et al, 2011, Faunes et al, 2013, Aulicino et al, 2020, while suggesting that specific β -catenin perturbations cause a bias towards the endoderm lineage, in line with Lef-1 related results previously reported (Ye et al, 2017).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…teratomas from the mutants with the highest β -catenin transcriptional activity showed major differentiation defects in the neuroectoderm, dorsal mesoderm and endoderm lineages. Of note, results in (Kielman et al, 2002) (Lyashenko et al, 2011, Wray et al, 2011, Faunes et al, 2013, Aulicino et al, 2020, while suggesting that specific β -catenin perturbations cause a bias towards the endoderm lineage, in line with Lef-1 related results previously reported (Ye et al, 2017).…”
Section: Introductionsupporting
confidence: 73%
“…These negative feedback loops contribute to the emergence of nonlinear dynamics in the Wnt/β-catenin pathway, proved to be important in different biological and developmental aspects (see for a review), ESCs pluripotency and somatic cell reprogramming (Marucci et al, 2014, Aulicino et al, 2014, Ho et al, 2013, Kimura et al, 2016, Lluis et al, 2008. The role of the canonical Wnt pathway in early in vivo developmental stages and the requirement of its activation for ESC self-renewal have been a matter of intense research (Anton et al, 2007, Ying et al, 2008, Soncin et al, 2009, Wagner et al, 2010, Lyashenko et al, 2011, Wray et al, 2011, Faunes et al, 2013, Chatterjee et al, 2015, Ortmann et al, 2020, Tao et al, 2020, Theka et al, 2019, Aulicino et al, 2020. Pluripotency incompetence of β -catenin -/-ECSs has been reported in two independent studies (Anton et al, 2007, Wagner et al, 2010; this phenotype was contradicted later using newly generated β -catenin -/cell lines, which showed selfrenewal in both serum and 2i+LIF (hereafter called 2i/L), but presented some differentiation defects when LIF-deprived (Wray et al, 2011, Lyashenko et al, 2011, Aulicino et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…is initiated upon binding of Wnt ligands with the membrane receptor complex known as Frizzled/low-density lipoprotein receptor-related protein 5/6 (FZD/LRP) [59]. Interactions between Wnt ligands and FZD/LRP5/6 trigger disheveled (DSH) that switches off glycogen synthase kinase 3 β (GSK-3β) and enables β-catenin protein to be translocated into the nucleus, whereby it complexes with the binding T cell factor/lymphoid enhancer-binding factor (TCF/LEF) to stimulate the expression of target genes involved in osteogenesis, including RUNX2 [60,61] (Figure 3). Several Wnt ligands, including Wnt4, Wnt5a, Wnt6, Wnt10a and Wnt10b, are involved in initiating the Wnt/β-catenin cascade and stimulation of osteoblast differentiation [62][63][64].…”
Section: Msc Signaling Pathways In Osteogenic Differentiationmentioning
confidence: 99%
“…In addition, our data indicated that most general naive markers in L-ESCs were clustered with 2i/L-ESCs ( Figures S2 A and S2B), and primed markers in L-ESCs exhibit intermediate state between 2i/L-ESCs and EpiSCs ( Figure S2 C). Furthermore, β-CATENIN and ERK play central roles in balancing differentiation and self-renewal ( Aulicino et al., 2020 ); hence, we tested the β-CATENIN and ERK levels in L-ESCs. Notably, some WNT signaling-related genes and the protein level of β-CATENIN were differentially expressed in L-ESCs compared with 2i/L-ESCs ( Figures S2 D and S2E).…”
Section: Resultsmentioning
confidence: 99%